Colombian Elders and Their Use of Handheld Digital Devices - Ricardo-Barreto, Carmen; Cervantes, Marco; Valencia, Jorge; Cano-Barrios, John; Mizuno-Haydar, Jorge (Frontiers in Psychology, 2018)
Technological advances in the information and knowledge society have influenced and transformed economic, social and educational dynamics. Currently there are many digital gaps related to the access to technology, lack of digital literacy and social use. These gaps vary based on the population ages and become more notorious in elders. This digital illiteracy is making all technological developments of the XXI Century to be underused, not making possible to take advantage of all the possibilities that they offer to our society, in this case, to Colombia. This study aims at analyzing the penetration level and use of handheld digital devices, especially the cellular phone, in adult population, based on the 2016 national survey of life quality in Colombia, elaborated by Departamento Administrativo Nacional de Estadística-DANE, specifically on the module of ownership and use of ICT goods. Results of four age groups are compared: 32 years or under, from 33 to 45, from 46 to 59, and over 60. The total sample is 37047 inhabitants of the Colombian territory, grouped by regions (Antioquia, Bogota, Caribbean, Eastern Central, Orinoquia, Amazonia, Pacific, San Andres, and Valle del Cauca). Data have been analyzed by using descriptive and inferential statistical procedures, contingency tables analysis, and logistic regression, in order to identify and know the effect of age on the level of penetration and use of handheld digital devices when comparing results in young adults and older ones. Findings show that young adults use these technologies in a greater proportion when comparing to older adults, showing a significant correlation between age and the increase of the digital gaps of access and social use of handheld digital devices. Even when characteristics like country regions, level of education, and the urban or rural setting are taking into account, the probability of obtaining penetration and use of handheld digital devices decreases significantly when attaining old age.